Scaling Up Digital Transformation in Education: An Exploration of Teachers’ Capabilities in Implementing Distance Learning in Southeast Sulawesi, Indonesia - Pelenkahu,Dina P. (2022)
Due to the pandemic, teachers are forced to implement distance learning and equipped themselves with digital skills to accommodate the sudden shift from instructional classroom activities to digital and more innovative teaching and learning practices. To ensure that teachers can adapt and innovate during this disrupted era, an exploration of teachers’ experiences, challenges, and opportunities for quality training and capacity building during the distance education implementation need to be unpacked. This research thus has three empirical objectives: first, to unpack teachers’ challenges in implementing distance learning in Southeast Sulawesi, Indonesia; second, to explore how they perceive their capabilities and tackle challenges of digital transformation in education; and lastly, to examine contributing factors that influence teachers’ capabilities in implementing effective digital transformation in education. To achieve these objectives, this research reflected the experience of teachers by using qualitative methodology. Semi-structured interviews were conducted with 10 public senior high school teachers from 3 different regions in Southeast Sulawesi. Using the Capability Approach, this research analysed the teachers’ experiences by combining key elements from Nussbaum’s list of central capabilities and Sen’s instrumental freedoms. The presented results highlighted teachers' challenges in personal, technological, and pedagogical aspects. The results showed how teachers reinforce their resources and instrumental freedoms to foster their capability and enable the exploration of distance learning. Although, the minimum existence of institutional support affects teachers’ capabilities to achieve functionings in addressing their digital skills and literacy to adapt to the unprecedented circumstances of distance learning. The consideration of teachers’ agency and capabilities highlighted the need to facilitate their participatory rights to exercise educational freedoms in implementing distance learning and to ensure the effective implementation of digital transformation in education.
Keywords: Distance learning; digital transformation; teachers’ experiences; capability approach; Sulawesi; Indonesia